HABITAT LECHITOCLADIUM ANGUSTIOVUM PADA IKAN KEMBUNG PEREMPUAN (RASTRELLIGER BRACHYSOMA) DI PERAIRAN TELUK BANTEN DAN PELABUHAN RATU - Forcep Rio Indaryanto; Yusli Wardiatno (Jurnal Ilmu Pertanian Indonesia, 2014)
Lechitocladium angustiovum is fish helminth parasites in the digestive tract to the Rastrelliger genus. The habitat of helminth parasites divided into microhabitat and makrohabitat. Fish helminth parasites infections showed the interaction of extrinsic factors (hosts habitat) and intrinsic factors (biological host). The study was conducted in February-June 2013 in the waters of the Banten Bay (Banten Province) and Pelabuhan Ratu Bay (West Jawa Province). Microhabitat helminth parasites of L. angustiovum that infect R. brachysoma gastrointestinal tract is the stomach and intestines. The presence of fish helminth parasites in fish is mutually beneficial. Fish helminth parasites get food from the fish but its presence prevents other parasites that infect fish. The presence of these worms in the digestive tract is affected by the presence of copepode and small crustaceans that are influenced by the host biology (growth and gonad development) and environmental waters. The number of L. angustiovum from Banten Bay and Pelabuhan Ratu Bay was not significantly different because of the fish has genetically similar populations.